Angels make their hope here : a novel - Clarke, Breena (Little, Brown and Company, 2014)
"Russell's Knob is not paradise. But already in 1849 this New Jersey highlands settlement is home to a diverse population of blacks, whites, and reds who have intermarried and lived in relative harmony for generations. It is a haven for Dossie Bird, who has escaped north along the Underground Railroad and now feels the embrace of the Smoot family. Duncan Smoot presides as accidental patriarch, protector of his enterprising sister, Hattie, and his two rambunctious nephews. As Dossie busies herself with cleaning, cooking, and tending the chickens at Duncan's homestead, she wonders: Could this man, her rescuer--so godlike in her eyes, so much older than she--expect her to become his helpmeet? Tentatively, Dossie begins to put down roots--until a shocking act of violence propels her away from Russell's Knob and eventually into the mayhem of New York City's mean streets."--